Methylselenol formed by spontaneous methylation of selenide is a superior selenium substrate to the thioredoxin and glutaredoxin systems. - Aristi P Fernandes (Public Library of Science (PLoS), 2012)
Naturally occurring selenium compounds like selenite and selenodiglutathione are metabolized to selenide in plants and animals. This highly reactive form of selenium can undergo methylation and form monomethylated and multimethylated species. These redox active selenium metabolites are of particular biological and pharmacological interest since they are potent inducers of apoptosis in cancer cells. The mammalian thioredoxin and glutaredoxin systems efficiently reduce selenite and selenodiglutathione to selenide. The reactions are non-stoichiometric aerobically due to redox cycling of selenide with oxygen and thiols. Using LDI-MS, we identified that the addition of S-adenosylmethionine (SAM) to the reactions formed methylselenol. This metabolite was a superior substrate to both the thioredoxin and glutaredoxin systems increasing the velocities of the nonstoichiometric redox cycles three-fold. In vitro cell experiments demonstrated that the presence of SAM increased the cytotoxicity of selenite and selenodiglutathione, which could neither be explained by altered selenium uptake nor impaired extra-cellular redox environment, previously shown to be highly important to selenite uptake and cytotoxicity. Our data suggest that selenide and SAM react spontaneously forming methylselenol, a highly nucleophilic and cytotoxic agent, with important physiological and pharmacological implications for the highly interesting anticancer effects of selenium.